'I Am' : monotheism and the philosophy of the Bible - Glouberman, M. (University of Toronto Press, 2019)
"For whom was the Hebrew Bible written? How much truth does it contain? What, according to the Bible, is the place of men and women in the world? What connection is there between the Bible and morality? In 'I AM' Mark Glouberman supplies new answers to these old questions. He does this by establishing that the foundational scripture of the West is, first and foremost, a philosophical document, not a theological tract, nor yet the religious history of a nation. The author identifies the Bible's fundamental principle, the ontological principle of particularity. This principle, he shows, is what makes the Bible the revolutionary text that it is. God's 'I AM WHO I AM' asserts the principle, of which the Bible's deity is a personified form. God's self-identification also points to the real, anthropological, meaning of the ism called 'monotheism.' A portion of Glouberman's book is devoted to illustrating the Bible's live relevance in many of the areas where modern philosophers congregate, including moral philosophy, political philosophy, metaphysics, and epistemology. Isn't it a bit late in the day for the Bible's meaning to be revealed? Glouberman says that it's about time."--